2014
DOI: 10.1007/978-3-319-13704-9_30
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Know-How into the Linked Data Cloud

Abstract: This paper presents the first framework for integrating procedural knowledge, or "know-how", into the Linked Data Cloud. Know-how available on the Web, such as step-by-step instructions, is largely unstructured and isolated from other sources of online knowledge. To overcome these limitations, we propose extending to procedural knowledge the benefits that Linked Data has already brought to representing, retrieving and reusing declarative knowledge. We describe a framework for representing generic know-how as L… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 11 publications
(11 reference statements)
0
16
0
Order By: Relevance
“…We have evaluated the quality of our automatic integration against existing integration efforts and showed its superiority across all the dimensions considered, such as the quantity and the precision of the links. For a more detailed account of this framework see the forthcoming paper by P. Pareti et al [4]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have evaluated the quality of our automatic integration against existing integration efforts and showed its superiority across all the dimensions considered, such as the quantity and the precision of the links. For a more detailed account of this framework see the forthcoming paper by P. Pareti et al [4]. …”
Section: Resultsmentioning
confidence: 99%
“…Similarly to the DBpedia project [1], we focus our extraction on semi-structured resources. Semi-structured know-how resources, such as the articles available on WikiHow, 4 can be analyzed reliably, as they are explicitly divided into a number of steps, methods and requirements.…”
Section: Methodsmentioning
confidence: 99%
“…Further support for our hypothesis is provided by the existence of large instructional websites that contain instructions with this level of structure. Evidence of this has been provided by a large scale conversion of over 200,000 instructions from the wikiHow and Snapguide 7 websites into an rdf format using the prohow vocabulary [7]. This existing structure can be extracted and represented in rdf.…”
Section: Know-how Acquisitionmentioning
confidence: 99%
“…This discovery process can be performed in different ways. In a previous experiment, we automated the creation of links between different sets of instructions from wikiHow (in the prohow format) using Natural Language Processing and Machine Learning [7]. This showed that creating links between sets of prohow instructions can be achieved with high accuracy.…”
Section: Know-how Linkingmentioning
confidence: 99%
“…The above shortcoming is evident even in conceptually simpler KBs. For instance, the Web of Know-How dataset 5 [21] contains activities and instructions collected from Wi-kiHow and Snapguide. Although the vocabulary used to represent this knowledge is relatively simple (PROHOW 6 ), the generated instantiations encapsulate rich axiomatizations.…”
Section: Mereology Patternmentioning
confidence: 99%